Taming Anxiety Before Surgery: Video Education Reduces Pre-Operation Patient Anxiety - Wahyuni, Eko Sari; Ernawati, Naya; Hamarno, Rudi; Setyarini, Anggun; Almutairi, Reem Iafi (Inovasi Lokal, 2024)
Pre-operative anxiety is normal, but can have a negative impact on the patient's health. Therefore, it is necessary to educate patients who will undergo surgery to reduce their anxiety levels. Providing education through videos has proven effective in reducing anxiety, this is because video media allows the delivery of more interesting and interactive information. The purpose of this community service activity is to determine the effect of video education on the anxiety of pre-surgical patients at Lavalette hospital Malang City. This community service program consists of two stages, namely socialization to families of surgical patients and training in the application of nursing interventions, anxiety reduction education in preoperative patients. The effectiveness of the program is evaluated by pre-test and post-test methods. The result of this community service activity is that video education has proven effective in reducing anxiety of pre-operative patients. It can be concluded that video education is an effective way to reduce anxiety in pre-operative patients and needs to be widely applied in hospitals.